Operationalizing Equity in Surgical Prioritization - Wiebe, Kayla; Kelley, Simon; Fecteau, Annie; Levine, Mark; Blajchman, Iram; Zlotnik Shaul, Randi; Kirsch, Roxanne (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2023)
The allocation of critical care resources and triaging patients garnered a great deal of attention during the COVID-19 pandemic, but there is a paucity of guidance regarding the ethical aspects of resource allocation and patient prioritization in ‘normal’ circumstances for Canadian healthcare systems. One context where allocation and prioritization decisions are required are surgical waitlists, which have been globally exacerbated due to the COVID-19 pandemic. In this paper, we detail the process used to develop an ethics framework to support prioritization for elective surgery at The Hospital for Sick Children, Toronto, a tertiary pediatric hospital. Our goal was to provide guidance for the more value-laden aspects of prioritization, particularly when clinical urgency alone is insufficient to dictate priority. With this goal in mind, we worked to capture familial, relational, and equity considerations. As part of our institution’s concerted efforts to ethically and effectively address our surgical backlog, an ethics working group was formed comprising clinicians from surgery, anesthesiology, intensive care, a hospital bioethicist, a parent advisor, and an academic bioethics researcher. A reflective equilibrium process was used to develop an ethics framework. To this end, the same methodology was used to create a support for patient prioritization that identifies clinically and morally relevant factors for prioritization among medically similar surgical cases, with a substantive goal being to identify and redress health inequities in surgical prioritization, inasmuch as this is possible. While further steps are needed to validate several aspects of the framework, our research suggests that an ethics framework grounded in the practical realities of hospital operations provides consistency, transparency, and needed support for decisions that are often left to individual clinicians, as well as an opportunity to reflect upon the presence of health inequities in all domains of healthcare delivery.